Kurilna naprava na biomaso Mrzli studenec - Budkovič, Lojze (Gozdarski vestnik, 2009)
The article presents the project, montage and working of the biomass burning device in the period 2001 - 2008.
Keywords: kurilne naprave; biomasa; sekanci